2015
DOI: 10.1177/1089253215572699
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Noninvasive Ventilation Following Cardiothoracic Surgery

Abstract: Postoperative pulmonary complications following cardiac and thoracic surgery are common and associated with significant morbidity and mortality. Noninvasive ventilation has emerged as a successful and well-validated strategy to treat various acute medical conditions. More recently, noninvasive ventilation has been studied in selective surgical patient populations with the goal of preventing postoperative complications and treating acute respiratory failure. In this clinical review, we will briefly examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Another study also reported different predictors for postoperative respiratory failure that included pneumonia, prolonged intubation >48 hours and reintubation; age >65 years, preoperative CHF, preoperative arterial pO2, duration of CPB, phrenic nerve injury and postoperative AKI were independent risk predictors . The ability to identify patients at risk of developing CS‐PRF will allow clinicians to provide preventive measures to minimize CS‐PRF such as preoperative pulmonary treatment, advocating smoking cessation, intraoperative ventilation strategies, intensive postoperative assessment for early extubation, postoperative non‐invasive ventilation and postoperative reversal of neuromuscular blocking agents …”
Section: Discussionmentioning
confidence: 99%
“…Another study also reported different predictors for postoperative respiratory failure that included pneumonia, prolonged intubation >48 hours and reintubation; age >65 years, preoperative CHF, preoperative arterial pO2, duration of CPB, phrenic nerve injury and postoperative AKI were independent risk predictors . The ability to identify patients at risk of developing CS‐PRF will allow clinicians to provide preventive measures to minimize CS‐PRF such as preoperative pulmonary treatment, advocating smoking cessation, intraoperative ventilation strategies, intensive postoperative assessment for early extubation, postoperative non‐invasive ventilation and postoperative reversal of neuromuscular blocking agents …”
Section: Discussionmentioning
confidence: 99%
“…The poor performance of the chest radiography is easily explained by the high incidence of bilateral posterobasal consolidations (94% in our study) in mechanically ventilated patients following cardiac surgery. [32] As previously reported 19 , bilateral radiological in ltrate and coalescent B2 lines due to hydrostatic pulmonary edema were present in 30% of our patients on ECMO VA [33], complicating the chest radiography interpretation. These results support the concept that combining ultrasound and clinical criteria is more discriminating than combining radiological and clinical criteria for the diagnosis of pneumonia in patients on VA ECMO.…”
Section: Components Of Scpis and Lus-scpis: Diagnostic Value In Patients On Va Ecmomentioning
confidence: 53%
“…The poor performance of the chest radiography is easily explained by the high incidence of bilateral postero-basal consolidations (94% in our study) in mechanically ventilated patients [ 30 ]. As previously reported, bilateral radiological infiltrate and coalescent B lines due to hydrostatic pulmonary edema were present in 30% of our patients on ECMO VA [ 31 ], complicating the chest radiography interpretation.…”
Section: Discussionmentioning
confidence: 99%